Toxicity of the genus Dinophysis in mariculture of the Guaynuná Bay, Ancash, Peru - Luján Bulnes, Luis Angelo; Departamento de Pesquería. Universidad Nacional de Trujillo, Trujillo, PERÚ (2023)
Dinophysis species causing various proliferations are part of the episodes of toxic microalgae, which generate a large negative impact on human health, marine ecosystems and related economic activities. In this paper we present the relationship of the toxicity of gender Dinophysis in mariculture of Guaynuna bay during 2015, through certain cell concentrations and toxicity testing of organisms in culture (shellfish). Four species of Dinophysis was determined: D. acuminata, D. caudata, D. rotundata and D. tripos; positive presence of lipophilic toxins, maximum concentrations during the summer Dinophysis 400 cells / L, 840 cells / L, 320 cells / L, 480 cells / L and 640 cells / L at five stations; the average surface temperature reached 21.17 ° C; the average dissolved oxygen ranged between 10.77 mg / L and 0.27 mg / L in the water column. The study indicates that the area evaluated maintains low levels of species of the genus Dinophysis possibly to sound environmental management in mariculture.